La consolidation de l’Europe bleue : nouveau contexte international et nouveaux enjeux - Congar, Richard (Études internationales, 1987)
Each of the member states of the European Economic Community (EEC) has extended, through a common agreement, its own fishing grounds to 200 miles, thus leading to the creation, since 1977, of the Community waters whose exploitation would be subjected to the common fisheries policy of the EEC. The widespread extension of fishing grounds throughout Europe together with the state of overfishing in the North-East Atlantic have led the EEC to elaborate a policy in order to protect the interests of its member states, to make their fishing vessels competitive, and to ensure the stability of the fishing industry. This paper looks into the implementation of the fisheries policy of the EEC, internally — namely access s rights to Community waters, the coordination of markets and producers, aid to modernize the vessels - as well as regarding foreign countries with whom agreements are sought in order to maintain historic fishing rights - specially in the North Atlantic - or in order to develop new fishing grounds - specially along the West African coast and in the Indian Ocean - a quarter of the EEC catch is made outside Community waters. France is deeply committed to the orientations of the EEC fisheries policy due to the importance of its fleet of trawlers fishing outside French waters and to the potential catch in the exclusive economic zone of its departments and territories overseas. The compromise signed by member states in 1983 is an important step towards the establishment of a true « Europe Fisheries ».